ANALISIS KESALAHAN PENULISAN KATA PADA KARANGAN NARASI SISWA KELAS V SDN PANCAMARGA SEBAGAI ALTERNATIF BAHAN PEMBELAJARAN MENULIS KARANGAN - Putri Rahmawati, - (2023)
The rules of writing Indonesian become an important thing to discuss, therefore in the writing we need a guideline of write so that our writing can be understood and accepted by readers. As well as writing a narrativeessays, we need the skills to use capital words that are in PUEBI. Narration of narrative writing activities are often carried by students at school. As a language learner, they are often made language mistakes where one of them is an error in word writing. Therefore, the researcher is interested to review research into language error analysis in the use of word writing in order to find out to what extend of students abilities and skills to words writing in the narrative essays and aims to make an appropriate learning material to anticipate similar errors to occurred next. In this research, the researcher used a synchronous approach. The data analysis techniques use the results of modifications according to Tarigan namely collecting data, identifying and classifying errors, increasing errors, explaining errors, estimating or predicting areas or grains of language that are prone, predicting the level of language learned that has the potential to cause errors, and correcting errors. From the analysis of the research results of students narrative essays, there are 83 errors in affix spelling, 14 errors repeated spelling and 225 errors word spelling. As for the result of the data analysis of these findings, the researcher made a learningmaterials to writing narrative essays in the class V of elementary school. Keyword: errors in word writing. Narrative essays